A clinician survey of use assessment, documentation, and education about cannabis in persons with cystic fibrosis. Issue 9 (16th July 2021) - Muirhead, Corinne A; Palmrose, Wendy; Condren, Michelle; Rotolo, Shannon M.; Pettit, Rebecca S.; Gill, Mohsain; Phan, Hanna
Abstract: Introduction: To help open the clinician dialogue regarding cannabis use in persons with cystic fibrosis (CF) in the United States, we aimed to describe current practices of use assessment and documentation processes related to cannabis. Methods: A cross‐sectional, anonymous survey study was distributed via email to CF directors and coordinators and to the Cystic Fibrosis Foundation (CFF) listservs of nurse, pharmacist, dietitian, social worker, and psychology care team members. The survey tool included multiple choice, scaled, and open‐ended items, which assessed participants' awareness of current cannabis laws in their state, prescribing practices for medical marijuana, screening and documentation practices, knowledge of and what indications participants believe cannabis and cannabidiol (CBD) could be beneficial. Data were analyzed using descriptive statistics. Results: There were 282 survey participants, with majority as providers (28%) and social workers (29%), representing all US regions. Participants varied in terms of frequency of evaluating cannabis use, with 15.4% "always, " 48.4% "sometimes, " and 41% "rarely, " or "never" asking about it. Regarding recreational versus medical cannabis use, 55.4% and 62.5% reported documentation of each type in the medical record, respectively. Participants reported appetite, pain, and nausea as the top three advocated indications for use. About 35% and 72% of participants felt "slightly" or "not at all" prepared to answer patient/family questions about cannabis and CBD, respectively. Conclusions: The approach to cannabis use assessment, documentation, and education across CF care centers is variable. There is a need for care team and patient/caregiver education materials about cannabis/CBD and CF.